2015
DOI: 10.1016/j.bcp.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potent and compartment-selective small molecule furin inhibitors using cell-based assays

Abstract: The proprotein convertase furin is implicated in a variety of pathogenic processes such as bacterial toxin activation, viral propagation, and cancer. Several groups have identified non-peptide compounds with high inhibitory potency against furin in vitro, although their efficacy in various cellbased assays is largely unknown. In this study we show that certain guanidinylated 2,5-dideoxystreptamine derivatives exhibit interesting ex vivo properties. Compound 1b (1,1'-(4-((2,4-diguanidino-5-(4-guanidinophenoxy)c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 68 publications
2
20
0
Order By: Relevance
“…Analysis of these data indicated that the replacement of the linkers containing the propoxy group (compounds 3b, k i = 1.70 μM and 3c, k i = 2.69 μM), on the "bridges" with the phenyl ring (compounds 6a, k i = 1.07 μM and 6b, k i = 0.74 ± 0.08 μM), led to an increase in the inhibitory effect of the compounds. This conclusion coincides with the results of studies previously pub- [20,26] lished by our group [17] and by other investigators of guanidilated aromatic compounds [27]. Among the derivatives (3a-c) with the amidinohydrazone group unsubstituted on the Megroup, the most active inhibitor was compound 3b (k i = 1.70 μM), which contains a positively charged group in the meta-position relative to the linker.…”
Section: -({[4-(4-{4-[(carbamimidamidoimino)methyl]phenoxy}phenoxy)psupporting
confidence: 80%
“…Analysis of these data indicated that the replacement of the linkers containing the propoxy group (compounds 3b, k i = 1.70 μM and 3c, k i = 2.69 μM), on the "bridges" with the phenyl ring (compounds 6a, k i = 1.07 μM and 6b, k i = 0.74 ± 0.08 μM), led to an increase in the inhibitory effect of the compounds. This conclusion coincides with the results of studies previously pub- [20,26] lished by our group [17] and by other investigators of guanidilated aromatic compounds [27]. Among the derivatives (3a-c) with the amidinohydrazone group unsubstituted on the Megroup, the most active inhibitor was compound 3b (k i = 1.70 μM), which contains a positively charged group in the meta-position relative to the linker.…”
Section: -({[4-(4-{4-[(carbamimidamidoimino)methyl]phenoxy}phenoxy)psupporting
confidence: 80%
“…General inhibitors of PCs such as PDX and CMK have been used with success in in vitro and in vivo experimental settings . Several putative furin‐specific inhibitors that have promising properties have been recently proposed . Therapies using an autologous tumor‐based product containing a plasmid encoding granulocyte‐macrophage colony‐stimulating factor and a bifunctional short hairpin RNAi that targets furin called FANG or Vigil have been or are being evaluated in clinical trials with patients suffering from advanced cancer of the ovary, liver and sarcomas .…”
Section: Discussionmentioning
confidence: 99%
“…After the development of these derivatives to dideoxystreptamine, other groups developed the bisguanidinephenyl ethers derivatives of 2–5 dideoxystreptamine containing two guanidine residues [57]. These two positively charged guanidine group are attached to a phenyl group, respectively, and the guanidine phenyl moieties are linked by a three carbon bridge.…”
Section: Paralyzing the Master Switches: Inhibition Of Pcsmentioning
confidence: 99%